2016
DOI: 10.1073/pnas.1607178113
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary alphabet for the observable protein structural universe

Abstract: Here, we systematically decompose the known protein structural universe into its basic elements, which we dub tertiary structural motifs (TERMs). A TERM is a compact backbone fragment that captures the secondary, tertiary, and quaternary environments around a given residue, comprising one or more disjoint segments (three on average). We seek the set of universal TERMs that capture all structure in the Protein Data Bank (PDB), finding remarkable degeneracy. Only ∼600 TERMs are sufficient to describe 50% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 75 publications
0
97
0
Order By: Relevance
“…The search was performed by full-backbone RMSD, with the cutoff chosen automatically, as reported previously [20], based on the complexity of the query motif (see S1 Text). …”
Section: Methodsmentioning
confidence: 99%
“…The search was performed by full-backbone RMSD, with the cutoff chosen automatically, as reported previously [20], based on the complexity of the query motif (see S1 Text). …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, universal structural degeneracies could apply equally well to evolutionarily ancient, relatively novel, or even engineered proteins. In our own work, we have shown that the presence and location of multi-segment TERMs can be identified within proteins based purely on sequence information [34]. We built sequence models for each multi-segment TERM, from corresponding structural matches, and scored all alignments in previously unseen sequences to identify likely TERM positions.…”
Section: Protein Structure Predictionmentioning
confidence: 99%
“…We have developed efficient structure search algorithms, MaDCaT and MASTER, that find all matches to a given query, composed of one or more disjoint segments, within a user-specified similarity cutoff [31,32]. We have used MASTER, which searches by backbone RMSD, to describe and take advantage of higher-order degeneracies [33,34]. Towards this, we adopted a common definition of a motif that captures the secondary, tertiary, and quaternary structural environments around a given central residue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations